2005
DOI: 10.1128/cdli.12.10.1145-1151.2005
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Microsphere-Based Serologic Multiplexed Fluorescent Immunoassay and a Reverse Transcriptase PCR Assay To Detect Murine Norovirus 1 Infection in Mice

Abstract: Murine norovirus 1 (MNV-1) is a newly recognized pathogen of mice that causes lethal infection in mice deficient in components of the innate immune response but not in wild-type 129 mice. In this study, in vitro-propagated MNV-1 was used as antigen to develop a multiplexed fluorescent immunoassay (MFI) to detect antibodies to MNV-1 in infected mice. The MNV-1 MFI was 100% specific and 100% sensitive in detecting anti-MNV-1 antibody in sera from experimentally infected mice. Testing of a large number of mouse s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
124
2
20

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 26 publications
3
124
2
20
Order By: Relevance
“…First, MNV may establish a persistent infection in certain immunodeficient mice, and prolonged human norovirus infection in immunocompromised patients has been documented (Nilsson et al, 2003;Gallimore et al, 2004;Rodriguez-Guillen et al, 2005). It is not known whether immunocompetent hosts can maintain a persistent norovirus infection, but it was noteworthy that following oral challenge of immunocompetent mice with MNV-1, viral genome was detected in mesenteric lymph nodes, jejunum and spleen in a portion of wild-type CD1 mice as long as 5 weeks after infection (Hsu et al, 2005(Hsu et al, , 2006. It should be noted that persistent infection of immunocompetent cats with a related virus, feline calicivirus (FCV), is well documented and the virus persists in the tonsils of infected animals (Wardley and Povey, 1977;Povey, 1986;Dick et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…First, MNV may establish a persistent infection in certain immunodeficient mice, and prolonged human norovirus infection in immunocompromised patients has been documented (Nilsson et al, 2003;Gallimore et al, 2004;Rodriguez-Guillen et al, 2005). It is not known whether immunocompetent hosts can maintain a persistent norovirus infection, but it was noteworthy that following oral challenge of immunocompetent mice with MNV-1, viral genome was detected in mesenteric lymph nodes, jejunum and spleen in a portion of wild-type CD1 mice as long as 5 weeks after infection (Hsu et al, 2005(Hsu et al, , 2006. It should be noted that persistent infection of immunocompetent cats with a related virus, feline calicivirus (FCV), is well documented and the virus persists in the tonsils of infected animals (Wardley and Povey, 1977;Povey, 1986;Dick et al, 1989).…”
Section: Discussionmentioning
confidence: 99%
“…All mice in this study originated from animal rooms in which antibodies to MNV had been detected in sentinel mice. In facility 2, there was a high (up to 80%) prevalence of antibodies to MNV in sentinel mice (female Swiss-Webster) that were housed in the same animal room as the Rag2 −/− mice for several months, as detected by a microsphere-based serological multiplexed fluorescent immunoassay conducted at the University of Missouri Research Animal Diagnostic Laboratory (Hsu et al, 2005). Sentinel mice in the rooms at both facilities were negative for antibodies to other known mouse pathogens (Sendai virus, reovirus type 3, Theiler's mouse encephalomyelitis virus, mouse hepatitis virus, ectromelia virus, epizootic diarrhea of infant mice, mouse cytomegalovirus, polyoma virus, pneumonia virus of mice, K virus, orphan parvovirus and mouse adenovirus).…”
Section: Pathologymentioning
confidence: 99%
See 1 more Smart Citation
“…In these cases, a molecular detection technique such as PCR/RT-PCR is efficacious. A microspherebased, multiplexed fluorescent immunoassay has been recently developed as a high-throughput, automated screening test to complement traditional ELISA in laboratory animal medicine [7,15]. The antibody response judged by ELISA was correlated with the titer measured by the IFA assay during acute MNV-S7 infection.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of a large number of mouse serum samples from research colonies in the United States and Canada identified MNV-1 reactive antibodies in 22.1% of serum samples [7]. In addition, the results of a serological survey that evaluated the contemporary prevalence of MNV in laboratory mice in Western Europe indicated that MNV is the most prevalent viral pathogen [13].…”
Section: Introductionmentioning
confidence: 99%